Endosonographic appearance of the anal sphincters in patients following colostomy - Sudoł-Szopińska, Iwona (Radiology and oncology (Ljubljana), 2002)
Background. The aim of the study was to visualize, by anal ultrasound (AUS), the suspected defects of the anal sphincters in the patients after colostomy and to analyze possible factors that could have led to such defects. Patients and methods. AUS, using a 7.0 MHz endorectal probe, was performed in a group of 25 patients with colostomy. The internal anal sphincter (IAS), external anal sphincter (EAS) and puborectalis muscle (PR) were visualized and the defects within them were qualified and quanttfied. For statistical analysis, the analysis of variance (ANOVA) was used. Results. The IAS was thin in all but three patients (22 patients; 88 %) with the mean thickness of 1.62 mm. A circular reduction of the thickness along the entire length of the IAS was seen in 20 patients (90.9 %). The echogenicity of the IAS was increased in 15 patients (60 %), and in 10 of them (66.6 ž), this defect embraced the whole length and circumference of the IAS. The margins of the 1AS were not well-defined in 10 patients (40 %). A significant correlation was found between the length of the patient's life with the stoma and the IAS echogenicity defect (p-value = 0.0001). No significant correlation was found between the dynamic examination, the IAS thickness and the IAS borders definition. Conclusion. The reduced thickness, increased echogenicity and borders definition defect of the IAS are seen in the patients after colostomy.The only significant correlation was confirmed between the length ofthe patient's life with the stoma and the IAS echogenicity defect.
Keywords: Analiza variance; analni sfinkter; Analysis of variance; Anus; Colostomy; Kolostomija; Ultrasonography; ultrazvočna diagnostika